Seagrass As A Leading Commodity To Drive The Sustainable Fisheries Sector In Sulampua - Jusniar, Jusniar; Nugroho, Wisnu Adi Agung (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
The aquaculture sector is a potential sector because it has long-term outputs with minimal risk. One of the best commodities in the aquaculture sector is seaweed. Indonesia, the world’s largest exporter of seaweed makes this commodity has an incridible value as gold. Furthermore, its high economic value and international trade potential solidify seaweed's nickname as 'green gold'.. Sulampua as the heart of seaweed producers should be able to maximize the potential of this commodity. The economic conditions of the fishing sector have been fluctuating over the last decade. A study of the blue economy is needed to maximize the potential of fishing potential commodities to accelerate economic growth sustainably. This research aims to look at a general view of the potential commodities of seaweed as green gold in the ocean of Sulampua. The variables used to measure seaweed's potential for economic growth in Sulampua are the value of seaweed production, the weight of seaweed production, the number of households in seaweed farming, and the amount of seaweed fishermen. The method used to analyze the impact of seaweed commodity variables on the economic growth of the fishing sector is panel data regression analysis with the Random Effect Model (REM). The selected model shows R-Squared value of 0,4470, which means that 44.70% of the model can explain the influence of the independent variable on the dependent variable. The results show that the variables value of seaweed production and the weight of seaweed production has a significant impact on the economic growth of the fishing sector.